Solving the flow shop scheduling problem under evolutionary approaches - Vilanova, Gabriela (2001)
The flow shop scheduling problem (FSSP) [12], has held the attention of many researchers. In a simplest usual situation, a set of jobs must follow the same route to be executed on a set of machines (resources) and the main objective is to optimize some performance variable (makespan, tardiness, lateness, etc.). In the case of the makespan, it have been proved that when the number of machines is greater than or equal to three, the problem is NP-hard.